Technical and Fundamental Analysis of Insurance Stock Prices on the Indonesian Stock Exchange (2018–2022) - Siti Fauziah Hanipah; Palti Marulitua Sitorus; Willy Sri Yuliandhari; Suhal Kusairi (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study was conducted to determine the influence of fundamental (ROA, TATO, DER, NPM, and EPS) and technical (past share price, share volume, and past share volume) variables on share prices. in insurance companies listed on the IDX. Purpose: This study aims to analyze the effect of fundamental variables (ROA, TATO, DER, NPM, EPS) and technical variables (past share price, share volume, past share volume) on stock prices of insurance companies listed on the Indonesia Stock Exchange (IDX). Research methodology: The study uses secondary panel data consisting of quarterly financial reports from 11 insurance companies during the 2018–2022 period. Panel data regression analysis with a fixed effects model was employed to test the relationship between the variables. Results: The findings show that TATO, DER, past share prices, and share volume have a positive and significant influence on stock prices, while past share volume has a significant negative effect. ROA, NPM, and EPS do not significantly affect stock prices. The F-test confirms that fundamental and technical variables together significantly influence stock prices. Conclusions: Both fundamental and technical indicators are crucial in determining stock prices of insurance companies, supporting their use in investment evaluations. Limitations: The study only covers non-reinsurance insurance companies listed on the IDX that consistently published quarterly reports from 2018 to 2022 and were not delisted during the period. Contribution: This study provides practical insights for investors in evaluating and selecting insurance stocks using combined fundamental and technical analysis.